Genealogy and biopolitics: epistemological choices in analyses of educational policies - Raquel A. L. S. Venera (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2016)
This article aims to socialize an epistemological choice in analyses of educational policies based on genealogy and biopolitics concepts, mainly according to Michel Foucault (2002, 2008), and the latter one to Antônio Negri and Michel Hardt (2004, 2005), as a powerful alternative to debate the epistemological approaches and perspectives in the analyses of policies field. It is proposed that do research in educational policies is, ultimately, a place of compliment to the creation and build of new knowledge in educational policies. It will be presented issues that came up in researches from the line of research Culture, Youth and Subjectivity Production, from Univille's Educational Policies and Practices Research Group, GPPPE, and that were extended in new research fronts in which other creations are in act.